Disruption of the RNA exosome reveals the hidden face of the malaria parasite transcriptome. Issue 9 (2nd September 2018) - Droll, Dorothea; Wei, Guiying; Guo, Gangqiang; Fan, Yanting; Baumgarten, Sebastian; Zhou, Yiqing; Xiao, Youli; Scherf, Artur; Zhang, Qingfeng
ABSTRACT: Antisense transcription emerges as a key regulator of important biological processes in the human malaria parasite Plasmodium falciparum . RNA-processing factors, however, remain poorly characterized in this pathogen. Here, we purified the multiprotein RNA exosome complex of malaria parasites by affinity chromatography, using HA-tagged PfRrp4 and PfDis3 as the ligands. Seven distinct core exosome subunits (PfRrp41, PfMtr3, PfRrp42, PfRrp45, PfRrp4, PfRrp40, PfCsl4) and two exoribonuclease proteins PfRrp6 and PfDis3 are identified by mass spectrometry. Western blot analysis detects Dis3 and Rrp4 predominantly in the cytoplasmic fraction during asexual blood stage development. An inducible gene knock out of the PfDis3 subunit reveals the upregulation of structural and coding RNA, but the vast majority belongs to antisense RNA. Furthermore, we detect numerous types of cryptic unstable transcripts (CUTs) linked to virulence gene families including antisense RNA in the rif gene family. Our work highlights the limitations of steady-state RNA analysis to predict transcriptional activity and link the RNA surveillance machinery directly with post-transcriptional control and gene expression in malaria parasites.